Role of oxidative stress in the apoptosis of hepatocellular carcinoma induced by combination of arsenic trioxide and ascorbic acid - Li Jing-jing; Tang Qiang; Li Yuan; Hu Ben-rong; Ming Zhang-yin; Fu Qin; Qian Jia-qing; Xiang Ji-zhou (Acta Pharmacologica Sinica, 2016)
Aim: The present study was designed to determine the possible pathway underlying the enhancement of apoptosis induced by the combined use of arsenic trioxide (As2O3) and ascorbic acid (AA). Methods: The level of intracellular reactive oxygen species (ROS) was detected by means of flow cytometry analysis with an oxidation-sensitive fluorescent probe (6-carboxy-2',7'dichlorodihydrofluorescein diacetate) uploading. The activity of glutathione (GSH), glutathione peroxidase (GPx), and superoxide dismutase (SOD) were detected by biochemical methods. The mitochondrial membrane potential was measured by flow cytometry analysis with rhodamine 123 staining. Bcl-2, Bax, and p 17 subunit of caspase-3 were analyzed using the Western blot method. The apoptosis rate was determined by flow cytometry with annexin-V/propidium iodide staining. Results: Compared with As2O3 (2.0 μmol/L) treated alone, As2O3 (2.0 μmol/L) in combination with AA (100 μmol/L) decreased intracellular GSH content from 101.30±5.76 to 81.91±3.12 mg/g protein, and increased ROS level from 127.61±5.12 to 152.60±5.88, which was represented by the 2, 7-dichlorofluorescein intensity. The loss of mitochondria membrane potential was increased from 1269.97±36.11 to 1540.52±52.63, which was presented by fluorescence intensity. The p17 subunit of caspase-3 expression was increased approximately 2-fold. However, SOD and GPx depletion and the ratio of Bcl-2 to Bax were equal to that of As2O3 treated alone (P>0.05). When the ROS scavenger, N/em>-acetyl-L/em>-cysteine, was added to As2O3 and AA combined treatment group, the apoptosis rate decreased from 15.60 %±1.14% to 9.48%±0.67%, and the ROS level decreased from 152.60±5.88 to 102.77±10.25. Conclusion: AA potentiated As2O3-induced apoptosis through the oxidative pathway by increasing the ROS level. This may be the result of depleting intracellular GSH. It may influence the downstream cascade following ROS, including mitochondria depolarization and caspase-3 activation. However, SOD and GPx depletion and the ratio of Bcl-2 to Bax influenced by As2O3was not found to be potentiated by AA.